1998
DOI: 10.1103/physrevb.57.2108
|View full text |Cite
|
Sign up to set email alerts
|

Fully self-consistentGWself-energy of the electron gas

Abstract: We present fully self-consistent results for the self-energy of the electron gas within the GW approximation. This means that the self-consistent Green's function G, as obtained from Dyson's equation, is used not only for obtaining the self-energy but also for constructing the screened interaction W within the random-phase approximation. Such a theory is particle and energy conserving in the sense of Kadanoff and Baym. We find an increase in the weight of the quasiparticle as compared to ordinary non-self-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
357
3
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(380 citation statements)
references
References 13 publications
(10 reference statements)
18
357
3
1
Order By: Relevance
“…Comparing Eqs. (3) and (8), one can still find a correspondence between the unperturbed energies of particle orbitals and the excitation spectrum {n} of the system with A + 1 nucleons and between the hole energies and the spectrum {k} of A − 1 nucleons. However, a larger number of states can appear in the correlated systems due to the mixing of sp excitations with more complicated configurations.…”
Section: Formal Development 21 Single-particle Green's Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparing Eqs. (3) and (8), one can still find a correspondence between the unperturbed energies of particle orbitals and the excitation spectrum {n} of the system with A + 1 nucleons and between the hole energies and the spectrum {k} of A − 1 nucleons. However, a larger number of states can appear in the correlated systems due to the mixing of sp excitations with more complicated configurations.…”
Section: Formal Development 21 Single-particle Green's Functionmentioning
confidence: 98%
“…While the propagator or Green's function method was the most important tool in the formal development of many-body theory [2] - [6], only in the last ten years has it been applied to many-body problems beyond its meanfield implementation (the Hartree-Fock approximation). Examples of such applications have appeared in atomic [7] and condensed matter physics [8]. In the atomic case, the essential new development involves taking the self-consistent determination of the electron propagator from the Hartree-Fock level to the fully self-consistent inclusion of the second-order self-energy.…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree well with previous results obtained with the fluctuation-exchange approximation 69 and with GW studies of the homogeneous electron gas, which showed that self-consistency in the GW self-energy washed out the satellite structure in the spectrum. 70 …”
Section: A Equilibrium Spectral Functionmentioning
confidence: 99%
“…Therefore, model systems that permit numerically exact or, ideally, analytic solutions play an important role for developing and testing approximation schemes within many-body perturbation theory, but even the homogeneous electron gas, a frequently employed model in solid-state physics, can only be treated numerically in the GW approximation. Furthermore, with no experimental measurements or independent theoretical benchmark results, even the basic question whether the true occupied band width in the range of metallic densities is smaller than that of free electrons, as predicted by the standard non-self-consistent GW approximation, 5,39 or larger, as obtained when full self-consistency is included, 7,8 is not yet finally settled. Calculations that go beyond the GW approximation and attempt to incorporate the combined effects of self-consistency and vertex corrections remain inconclusive, because the results depend on the choice of vertex function and details of the implementation.…”
Section: Introductionmentioning
confidence: 99%
“…One long-standing controversy centers on the question whether the Green function used to construct the self-energy should be evaluated selfconsistently or not. [7][8][9][10][11][12][13][14][15][16][17] Both approaches can be justified:…”
Section: Introductionmentioning
confidence: 99%